Identifying prioritised actions for improving dysphagia services in Singapore: Insights from concept mapping with patients and caregivers - Poon, Flora M. M.; Ward, Elizabeth C.; Burns, Clare L. (International journal of language & communication disorders, 2024)
Background Person‐centred services are inherently related to patients/caregivers’ needs. However, the extent to which dysphagia services within Singapore meet consumer needs is largely unknown. Involving patients/caregivers in service evaluation/redesign deepens the understanding of consumer needs. This process also increases the success of implementing service enhancements through relevant and meaningful change. Aim This study aimed to identify aspects of dysphagia services, within acute and subacute settings in Singapore, perceived as highly important and easy to change by patients/caregivers. Methods & Procedures Using concept mapping methodology, 5 patients and 11 caregivers reflected on their experiences of receiving dysphagia care and proposed 59 unique suggestions to improve dysphagia services within Singapore. Then, each individual sorted the suggestions into groups based on similarity and rated each statement for its perceived importance and changeability for service enhancement. Data were analysed using multidimensional scaling, hierarchical cluster analysis, and bivariate analysis to generate clusters of conceptually similar suggestions and a prioritised list of suggestions for service enhancement. Results Twelve clusters were identified, with most rated as more important than changeable for service improvement. Participants prioritised 23 (39%) of the suggestions as highly important and easy to change, and these focused on ensuring effective communication among consumers and healthcare team, enhancing patients and carers’ access to support at home, increasing patients and carers’ access to educational resources, and improving service quality and access through technology. Conclusion These findings provide future directions on how to develop and implement dysphagia services in Singapore to better meet the needs of patients/caregivers. WHAT THIS PAPER ADDS What is already known on this subject Little is known about patients and caregivers’ experiences and expectations of receiving dysphagia services in Singapore. Consulting them in service review and improvement deepens understanding of their needs and increases the success of implementing meaningful service enhancements. What this study adds to existing knowledge This study shows that patients and caregivers in Singapore identified a wide range of dysphagia service issues and prioritised a list of suggestions for service improvement. They prioritised four key areas for service optimisation: ensuring effective communication among consumers and healthcare team, enhancing patients and carers’ access to support at home, increasing patients and carers’ access to educational resources, and improving service quality and access through technology. What are the clinical implications of this work? This research highlights the importance of considering the consumers’ perspectives in service review and redesign. Patients and caregivers in Singapore identified four prioritised areas for service enhancements. These findings provide future directions on how to develop and implement dysphagia services in Singapore to better meet the needs of patients and caregivers.